Soil physical properties, nutrients, and crop yield with two-year tillage rotations under a winter wheat-summer maize double cropping system - Yin, Baozhong; Liu, Pan; Cui, Yongwei; Hu, Zhaohui; Li, Xiangling; Pan, Zhihua; Zhen, Wenchao (International Journal of Agricultural and Biological Engineering, 2022)
Winter wheat and summer maize were planted from 2015-2017 to study the effects of different rotational tillage patterns on soil physicochemical properties, crop yield, water content, and fertilizer utilization. The tillage treatments were designed as wheat subsoiling-maize no tillage (WS-MN), wheat rotary tillage-maize subsoiling (WR-MS), wheat subsoiling-maize subsoiling (WS-MS), and conventional wheat rotary tillage-maize no tillage (WR-MN) as a control. Among the four treatments, WS-MN and WR-MS were single-season subsoiling treatments, and WS-MS was a two-season subsoiling treatment. The average soil bulk density decreased by 7.6% in the single- and double-season subsoiling groups compared to the WR-MN group, and the total porosity and noncapillary porosity increased by 10.7% and 12.2%, respectively. Single- or double-season subsoiling treatment was not conducive to water storage in the 0-20 cm soil layer but increased the water content of the 20-140 cm soil layer, and the average soil water content of the 0-140 cm layer was increased by 11.6% in the two-growing season treatment groups compared with the WR-MN group. In WS-MS and WS-MN groups compared with the WR-MN group, the soil ammonium nitrogen content was increased by an average of 18.6% in 0-20 cm soil and 16.8% in 20-100 cm soil; soil nitrate-nitrogen content was decreased by 13.5% in 0-100 cm soil; total organic carbon and microbial carbon contents in the 15-30 cm soil were increased by 18.1% and 12.7%, respectively; and soil urease, catalase, and alkaline phosphatase activities were increased by 46.1%, 15.2%, and 23.1%, respectively. Annual crop yield and water use efficiency increased by 8.9% and 15.0%, respectively, in both the single- and double-season subsoiling treatment groups. This study demonstrated the advantages of subsoiling tillage and suggested that it is suitable for crop cultivation in the Haihe Plain, China.Keywords: tillage rotations, wheat-maize double cropping, soil properties, utilization of water and fertilizer, crop yieldDOI: 10.25165/j.ijabe.20221501.6855Citation: Yin B Z, Liu P, Cui Y W, Hu Z H, Li X L, Pan Z H, et al. Soil physical properties, nutrients, and crop yield with two-year tillage rotations under a winter wheat-summer maize double cropping system. Int J Agric & Biol Eng, 2022; 15(1): 172–181.